Polydioxanone threads and neocollagenesis in the periorbital region: A narrative review of the literature (Research, Society and Development, 2025)
Polydioxanone (PDO) threads have gained popularity in facial aesthetics due to their ability to promote a lifting effect and stimulate neocollagenesis. In the periorbital region, where the skin is more delicate and signs of aging are more pronounced, these threads present a less invasive alternative compared to traditional surgical techniques. This narrative review of the literature aims to explore the efficacy and safety of PDO threads in the periorbital region, focusing on collagen production stimulation, aesthetic outcomes, and possible adverse effects. Through the analysis of various clinical studies and case reports, significant improvements in skin firmness and reduction of fine wrinkles were observed, with a low incidence of serious complications. However, there is still a lack of long-term data regarding the effects of PDO threads, especially in the periorbital region. Thus, further investigation is needed to confirm the durability of results and the safety of the procedure. It is concluded that, although promising, PDO threads require more scientific research to be fully understood in their periorbital application.